(untitled) (Journal of Medicine, 2008)
Systemic lupus erythematosus (LE) is a heterogeneous, multisystem, autoimmune disease characterized by the production of auto-antibodies against several cell constituents. The skin is one of the target organs most variably affected by the disease can be yield valuable diagnostic & prognostic information. The present study was conducted to evaluate cutaneous manifestations of SLE in Bangladeshi patients. 100 cases of SLE were collected from the Department of Dermatology, BSMMU, Dhaka. The diagnosis was based on American Rheumatism Association Criteria. Cutaneous changes were recorded on a predevised pro forma. LE specific cutaneous changes noted were: Malar rash or butterfly rash (70.0%), maculopapular rash (19.0%), discoid rash (10.0%), and bullous LE (10.0%). Non specific LE lesions noted were: Photosensitivity (75.0%), alopecia (47.0%), oral mucosal lesion (34.0%), hyperpigmentation (20.0%), nail change (15.0%), Raynauds phenomenon (12.0%), Palmar erythema, genital lesion, periungual talangiectesia, leg ulcers, livedo reticularis, erythema multiform were rare. Systemic lupus erythematosus is a multisystem disease that predominantly affects women. Cutaneous lesions are the most important diagnostic tools as reflected by the fact that they account for four of the 11 revised American Rheumatism Association criteria of SLE. The pattern of skin changes may vary from place to place. Key Words: SLE, LE specific and non specific cutaneous lesions Â DOI = 10.3329/jom.v8i2.1405 J MEDICINE 2007; 8 : 44-48